2015
DOI: 10.1016/j.ypmed.2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Lunch is in the Bag program on communication between the parent, child and child-care provider around fruits, vegetables and whole grain foods: A group-randomized controlled trial

Abstract: Objective To evaluate the effectiveness of the parent- and early care education (ECE) center-based Lunch is in the Bag program on communication between parent, child, and their ECE center providers around fruits, vegetables and whole grain foods (FVWG). Method A total of n=30 ECE center; 577 parent-child dyads participated in this group-randomized controlled trial conducted from 2011–2013 in Texas (n=15 ECE center, 327 dyads intervention group; n=15 ECE center, 250 dyads comparison group). Parent-child and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Communication of nutrition information with ECE children and parents was measured using 2 items from previous studies 20 —for example, “How often do you talk with children about the healthiness of their eating habits?” Response options ranging from 0 = never to 4 = every day.…”
Section: Methodsmentioning
confidence: 99%
“…Communication of nutrition information with ECE children and parents was measured using 2 items from previous studies 20 —for example, “How often do you talk with children about the healthiness of their eating habits?” Response options ranging from 0 = never to 4 = every day.…”
Section: Methodsmentioning
confidence: 99%
“… 27 Also, the content of the Jump2Health Website ™ , organized as 7 Healthy Habits, was based on current best practices and evidence analysis, including new factors related to childhood obesity, such as sleep. 7 , 8 Other obesity prevention research involving parents of preschool children has included only one or a few healthy habits simultaneously, such as a program focusing on fruits, vegetables, and whole grains 40 and a program focusing on sugar-sweetened beverage and juice intake. 41 Of these, only the latter program was designed to be delivered by e-Health.…”
Section: Resultsmentioning
confidence: 99%
“…An intervention study conducted in the United States reported that parent–child communication is benefited by preparing meals together because the children have the opportunity to ask their parents about the ingredients of healthy lunch recipes that are provided in school lunch programs [24]. Another study reported that liking of different foods of children was determined by food-related behaviors learned at a young age [25].…”
Section: Discussionmentioning
confidence: 99%